Etika Pendidik Menurut Al Quran dan Hadist: Penelitian - Juwairiyah; Miftahul Hamida; Faridatul Hasanah; Asmaul Khusnah; Abdurrahman (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the concept of teacher ethics according to the Qur’an and Hadith, as well as its relevance to the thoughts of KH Imam Zarkasyi and Imam Al-Ghazali in the context of modern Islamic education. The research method used is library research with a qualitative-descriptive approach. The primary sources include Qur’anic verses and the Prophet’s Hadiths, while the secondary sources consist of scholarly works—both classical and contemporary—discussing teacher ethics. The results indicate that the Qur’an positions teachers as moral guides and mentors who lead learners toward truth, as reflected in Surah As-Saff [61]: 2–3, which emphasizes consistency between words and actions. The Prophet’s Hadith also describes teachers as the heirs of the prophets, bearing profound moral and spiritual responsibility. The perspectives of KH Imam Zarkasyi and Imam Al-Ghazali reinforce this concept by highlighting sincerity, trustworthiness, exemplary conduct, and moral education as the essence of a teacher’s role. Therefore, this study concludes that teacher ethics in Islam are not merely professional obligations but also transcendental values that play a crucial role in shaping students’ character in the modern educational era.